Harmonia kakofonii, czyli co śpiewa Europa Środkowo-Wschodnia (o dialogu kultur w polskim przekładzie Ministerstwa Bólu Dubravki Ugrešić) - Majdzik, Katarzyna (Przekłady Literatur Słowiańskich, 2011)
The harmony of cacophony that is to say what Middle Eastern Europe sings (about culture dialogue in Polish translation of The Ministry of Pain written by Dubravka Ugrešić) Translation relies on the recontextualisation and interpretation of the original text. Different cultural, linguistic and historical impacts determine the foundation of the translator’s interpretation. Translation enables cross-cultural communication as it mediates between two cultures and two semantic universes. The aim of such a dialog is to experience the understanding of different sensitivity and to learn new forms of expression as well as ways of perceiving the world. The object is to develope one’s own interpretations of reality. According to Y. Winkin communication is a confirmation of collective values and relations of the group members belonging to the same culture. This statement results in understanding translationas a new symbolic order discovery and affirmation of the existing one. The issue of interpretation and culture communication „in” and „through” the translation is discussed in the article on the basis of the Polish translation of a novel written by Dubravka Ugrešić titled The Ministry of Pain